The Distribution of Hepatitis C Virus Genotypes, Viral Load and Antibody Titer among Iraqi Chronic Hepatitis Patients (Medico Legal Update, 2020)
The study was carried out for the purpose of investigating the microbial and mineral pollutants in the imported red meat. This research included field work and random sampling of the markets of Diwaniya Governorate. In addition, laboratory tests were carried out on samples from the following countries: (Saudi Arabia, Turkey, Jordan, Lebanon) in the laboratories of the Department of Life Sciences. Some bacterial species were investigated in the studied meat samples. Microbial contamination The results of the study showed a high level of bacterial content and the results were the emergence of Staph bacteria. aureus in the nutritious dish. The other dishes showed no growth due to the good storage of meat. The dish in which the bacteria appeared was due to poor storage or preservatives used in the storage process. As for the chemical analysis of heavy metals using the Atomic Absorption Spectrometer technique, the concentrations were as follows: Concentration of the copper component (0.013-0.310) ?g / g, while the concentration of the lead element (0.001-0.111) ?g / G; for cadmium, its concentration was 0.001-0.004 ?g / g and the concentration of chromium was 0.003-0.020 ?g / g. The results showed that levels of copper, lead, chromium and cadmium were higher than those allowed by the World Health Organization (WHO) and FAO in some imported meat samples.